Microbiology and Initial Antibiotic Therapy for Injection Drug Users and Non–Injection Drug Users with Cutaneous Abscesses in the Era of Community‐associated Methicillin‐resistant Staphylococcus aureus. (22nd July 2015) - Jenkins, Timothy C.; Knepper, Bryan C.; Jason Moore, S.; Saveli, Carla C.; Pawlowski, Sean W.; Perlman, Daniel M.; McCollister, Bruce D.; Burman, William J.; Merchant, Roland
Abstract Objectives The incidence of cutaneous abscesses has increased markedly since the emergence of community‐associated methicillin‐resistant Staphylococcus aureus (CA‐MRSA). Injection drug use is a risk factor for abscesses and may affect the microbiology and treatment of these infections. In a cohort of patients hospitalized with cutaneous abscesses in the era of CA‐MRSA, the objectives were to compare the microbiology of abscesses between injection drug users and non–injection drug users and evaluate antibiotic therapy started in the emergency department (ED) in relation to microbiologic findings and national guideline treatment recommendations. Methods This was a secondary analysis of two published retrospective cohorts of patients requiring hospitalization for acute bacterial skin infections between January 1, 2007, and May 31, 2012, in seven academic and community hospitals in Colorado. In the subgroup of patients with cutaneous abscesses, microbiologic findings and the antibiotic regimens started in the ED were compared between injection drug users and non–injection drug users. Antibiotic regimens involving multiple agents, lack of activity against MRSA, or an agent with broad Gram‐negative activity were classified as discordant with Infectious Diseases Society of America (IDSA) guideline treatment recommendations. Results Of 323 patients with cutaneous abscesses, 104 (32%) occurred in injection drug users. Among the 235 cases where at least one microorganism was identified by culture, S. aureus was identified less commonly among injection drug users compared with non–injection drug users (55% vs. 75%, p = 0.003), with similar patterns observed for MRSA (33% vs. 47%, p = 0.054) and methicillin‐susceptible S. aureus (17% vs. 26%, p = 0.11). In contrast to S. aureus, streptococcal species (53% vs. 25%, p < 0.001) and anaerobic organisms (29% vs. 10%, p < 0.001) were identified more commonly among injection drug users. Of 88 injection drug users and 186 non–injection drug users for whom antibiotics were started in the ED, the antibiotic regimens were discordant with IDSA guideline recommendations in 47 (53%) and 101 (54%), respectively (p = 0.89). In cases where MRSA was ultimately identified, the antibiotic regimen started in the ED lacked activity against this pathogen in 14% of cases. Conclusions Compared with non–injection drug users, cutaneous abscesses in injection drug users were less likely to involve S. aureus, including MRSA, and more likely to involve streptococci and anaerobes; however, MRSA was common in both groups. Antibiotic regimens started in the ED were discordant with national guidelines in over half of cases and often lacked activity against MRSA when this pathogen was present.